Analysis of Grondkaart as Land Ownership Rights in the Perspective of Land Law in Indonesia - Vitri Dini Artistry; Dewi Sulistianingsih (Universitas Negeri Semarang, 2024)
A land dispute case was experienced by residents of Kebonharjo, Tanjung Mas Village, Semarang City against the Indonesian Railways Limited Company (PT KAI), where PT. KAI claims that the Kebonharjo Residents' land belongs to PT. KAI with grondkaart as a proof base. The State Treasury Law is the main basis regarding grondkaart. Decision “No. 227/Pdt.G/2016/PN. Smg,” provides information that grondkaart is still legally valid. Meanwhile Law no. 5 of 1960 and Law no. 23 of 2007, provide mutual explanations regarding orders for making certificates for land rights. This article uses a normative juridical approach, and descriptive analysis of the basis of land ownership rights in the form of grondkaart. The research results show that a state based on Pancasila really prioritizes the value of material justice which originates from the will of the people who have a strong relationship with their land, so that it can be equated with human rights. The state cannot arbitrarily control people's land rights, and the law must be in accordance with the wishes of the community, namely as a form of service by the state, not a form of confiscation by the state. Grondkaart is not stronger than a land certificate, where the form of a land certificate is considered stronger because it contains the will of the community to transfer it consciously and is not a form of confiscation. From a normative juridical point of view, Indonesian land law does not adhere to legal positivism in which Indonesian society is united by the awareness in their souls to will on the basis of Pancasila, so that their will cannot be concretized by the state in the form of any regulations, but state regulations remain as a means of order and realizing shared prosperity.